Short-Term Efficacy and Safety of Non-Ablative Laser Treatment Alone or with Estriol or Moisturizers in Postmenopausal Women with Vulvovaginal Atrophy. Issue 5 (31st March 2022) - Alvisi, Stefania; Lami, Alessandra; Baldassarre, Maurizio; Lenzi, Jacopo; Mancini, Ilaria; Seracchioli, Renato; Meriggiola, Maria Cristina
ABSTRACT: Background: Among treatments for vulvo-vaginal atrophy (VVA), there is a new kind of energy-based device, the non-ablative CO2 laser. Aim: This study aimed to assess the efficacy and safety of the non-ablative CO2 laser in menopausal women with VVA as a monotherapy or in association with vaginal estriol or moisturizer. Methods: Seventy-five women with VVA received laser treatment (Laser group), laser plus estriol gel (Laser+E) or laser plus moisturizers (Laser+M). The study protocol consisted of 3 monthly laser sessions (t0, t1, t2) and a gynecological examination at baseline and 1 month after last laser treatment (t3). Objective measures included VHI (Vaginal Health Index) and VuHI (Vulvar Health Index); subjective symptoms of VVA (Dryness, Burning, Itching, Dysuria) evaluated via visual analog scales, sexual function evaluated by FSFI (Female Sexual Function Index), FSDS (Female Sexual Distress Score) and MENQOL (Mopause-specific Quality Of Life). Adverse events and discomfort encountered during the procedure were also assessed. Outcomes: Primary outcomes were the evaluation of VHI and VuHI and secondary outcomes were changes in VVA symptoms (VAS), sexual function (MENQOL, FSFI, FSDS) and discomfort during the procedure. Results: Seventy-five women (25 in Laser, 25 in Laser+E and 25 in Laser+M group) completed the study. At t3, mean VHI, VuHI, dryness, burning and itching VAS scores improved significantly with no differences between the groups. The lubrication domain of FSFI improved significantly only in the Laser+M group, while the pain domain improved significantly in all women with no differences between the groups. FSFI and FSDS overall scores and MENQOL sexual domain improved in all women with no significant difference between the groups. The mean score of the pain during the procedure was low at t0 and did not change throughout the study. Clinical implications: This study extends knowledge concerning the effectiveness of a new non-ablative CO2 laser in post-menopausal women with VVA. Strengths & limitations: This is one of the first studies on this kind of laser and is the first to compare the effectiveness of laser treatment alone or in combination with vaginal estriol or moisturizers. Parameters of VVA and sexual function were evaluated using validated tools. Study limitations include short follow-up time, the limited number of participants and the absence of a sham-controlled group. Conclusion: Non-ablative CO2 laser seems to be an effective treatment for VVA in menopausal women. Our preliminary data shows that it can be effective as monotherapy or with adjuvant treatments.